A review on importance of histological evaluation for cartilage tissue engineering - Md Nazir, Noorhidayah; Mohamad, Mohd Yusof; Abdul Rahman, Rozlin; Mohamad Sukri, Norhamiza; Ahmad Radzi, Muhammad Aa'zamuddin; Sha'ban, Munirah (2014)
Tissue engineering is a multidisciplinary field that applies its principles towards the development of a biological substitute or human spare part that restores, maintains and performs similar functions to the native tissue. Besides an increasing number of basic and applied researches carried out on cartilage, several tissue engineered cartilage products have successfully entered the international market including Carticel, ChondroCelect and Matrix-induced Autologous Chondrocytes Implantation (MACI) which approved by U.S. Food and Drugs Administration (FDA) and European Medicines Agency (EMA). Cartilage has limited healing capacity and lack inflammatory response due to its avascular nature. These characteristics make cartilage a suitable candidate for tissue engineering. Ultimately, the goal of cartilage tissue engineering is to treat joint diseases such as osteoarthritis and degenerative disc disease. Despite current advancement and achievement, basic laboratory evaluation is still necessary to develop the full potential of cartilage tissue engineering. Histological assessment is one of the most important microscopic evaluations used to assess the quality of the newly engineered cartilage tissue. The analyses may involve Haematoxylin and Eosin (H&E) staining to visualize overall cells and tissue organization or morphology, Alcian Blue staining and Safranin O to visualize accumulation of glycosaminoglycan and proteoglycan-rich matrix in cartilage, respectively. Other than those standard histological analyses, immunohistochemistry staining against certain cartilaginous markers for example Type I and II Collagen offers a remarkable and reliable assessment to the tissues. These histological assessments are being used to visualize primarily the histoarchitectural structure of the engineered cartilage tissue in comparison with the native cartilage. In most cases, the structure of a cellular or tissue component is often associated with its function. In fact, one mantra in anatomy and physiology encapsulates the idea perfectly - structure dictates function. Accordingly, other than providing reliable primary assessment, histological evaluation is indeed an important parameter to confirm the quality of a newly formed cartilage in terms of structure and function.